Chromosome karyotype analysis of Sapindus rarak (lerak) from Ungaran, Central Java, Indonesia - ANANDA PUTRI DEWANTARI MASAILLA; ENDANG YUNIASTUTI; PARJANTO PARJANTO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Masailla APD, Yuniastuti E, Parjanto. 2026. Chromosome karyotype analysis of Sapindus rarak (lerak) from Ungaran, Central Java, Indonesia. Biodiversitas 27 (6): d270620. https://doi.org/10.13057/biodiv/d270620. Sapindus rarak (lerak), a member of the family Sapindaceae and the soapberry group, has long been utilized as a natural cleaning agent due to its high saponin content. Despite its potential as an environmentally friendly and renewable resource, genetic information on this species remains limited. This study aimed to analyze the karyotype of S. rarak to provide fundamental cytogenetic data that can support plant breeding and conservation efforts. Two types of S. rarak, namely yellow and brown variants originating from Ungaran, Central Java, Indonesia, were used as research materials. Chromosome analysis was conducted using the squash preparation method, followed by microscopic observation and measurement of chromosome number, size, and centromere position. The data were analyzed descriptively to determine the karyotype characteristics. The results showed that both S. rarak types have the same chromosome number, 2n = 28, with chromosome sizes ranging from 0.856±0.145 to 2.487±0.222 µm. The karyotype formula was determined as 2n = 2x = 28 = 13m + 1sm, indicating a predominance of metacentric chromosomes. These findings provide essential baseline genetic information that can be used for species identification, support plant breeding programs, and contribute to the development of S. rarak as a sustainable, eco-friendly natural soap resource.